Why do oaths work? Image concerns and credibility in promise keeping - Sorravich Kingsuwankul; Chloe Tergiman; Marie-Claire Villeval (Tinbergen Institute, 2023)
We use a laboratory experiment to understand the channels through which honesty oaths can affect behavior and credibility. Using a game with asymmetric information in a financial market setting that captures some important features of advisor-investor interactions, we manipulate the common knowledge of the promise and investigate three non-pecuniary costs of breaking an oath: co-player image costs, audience-image costs, and self-image costs. For investors oaths are neither sufficient nor necessary to generate trust: ultimately investors rely on their experience. We link laboratory results to a survey we conducted in the Netherlands where oaths are required in the banking sector.
Keywords: C91; D01; D83; D91; 330; Promise-keeping; Honesty Oaths; Common Knowledge; Deniability; Financial Markets; Laboratory Experiment